The Effect of Water Spinach (Ipomoea aquatica), Watercress (Nasturtium officinale), and Genjer (Lemna minor) on Domestic Wastewater Quality - Lastri, Lastri; Tobing, Joshua H. L. (Jurnal Biologi Tropis, 2025)
Several types of aquatic plants are known to have the ability to improve water quality. The application of phytoremediation to domestic waste can significantly reduce Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), ammonia, nitrate, and phosphate levels, as well as increase dissolved oxygen (DO) levels in the water, thus improving water quality and making it suitable for aquatic organisms. This study investigated the efficacy of three aquatic plants Water Spinach (Ipomoea aquatica), Watercress (Nasturtium officinale), and Genjer (Lemna minor) in enhancing the quality of domestic wastewater. The experiment was conducted in a controlled environment at the Greenhouse facility of Universitas Advent Indonesia, utilizing seven containers stocked with domestic wastewater and catfish specimens. Treatments consisted of systems with and without the incorporation of these aquatic plants. Results demonstrated that all three plants significantly ameliorated water quality parameters, including reductions in Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), and Total Suspended Solids (TSS), alongside elevations in pH and Dissolved Oxygen (DO) levels. Notably, Ipomoea aquatica exhibited superior performance, yielding the highest catfish survival rates. These outcomes underscore the potential of integrating aquatic plants into aquaponic systems as aviable, environmentally sustainable approach to domestic wastewater remediation.